주얼리의 시장분석을 통한 Semiprecious Stone 제품 개발 연구 -가넷, 시트린 애머트린, 패리도트를 중심으로 - 이기상; Lee, Ki-Sang (한국콘텐츠학회 논문지, 12(4), 2012)
Recently, while sharing various values of an individual through fast information delivery with the consciousness change of consumers, the trend is now changing by needs of consumers from the trend that companies took the lead in the past. In addition, while jewelries are changed to fashion's consumer goods, it is time that the domestic jewelry industry also needs development of products applied with various colors and visual emotion that consumers demand. Accordingly, much interest in natural colorful gems and the consumption market are being increased in the jewelry industry. Accordingly, this research has progressed the necessity, the status analysis and consumer preference analysis of products development using Semiprecious Stone, and extracted the target market by style and needs of consumers through a consumer trend survey and image analysis survey for development of products. And, this research has set a design directionality by extracting adjectives that can be applied to design preference images by age. This study has confirmed the necessity and possibility of Semiprecious Stone products development based on the analysis of jewelry market. 최근 소비자의 의식 변화와 함께 빠른 정보 전달을 통해 개개인의 다양한 가치관을 공유하면서 과거 기업이 주도하던 트렌드에서 이제는 소비자의 Needs에 의해 트렌드가 변화하고 있다. 국내 주얼리 산업에서도 또한 주얼리가 패션 소비재로 변화하면서 소비자가 요구하는 다양한 칼라와 시각적 감성이 적용된 제품 개발이 필요한 시점이다. 이에 주얼리 산업에서는 천연 유색 보석에 대한 많은 관심과 그 소비시장이 확대되어지고 있는 실정이다. 이에 본 연구에서는 Semiprecious Stone을 이용한 제품 개발의 필요성과 현황분석, 소비자 선호도 분석을 진행하고, 제품 개발을 위해서 소비자동향 조사 및 이미지 분석 조사를 통해 소비자의 스타일과 Needs에 의한 표적시장을 추출하였다. 그리고 연령별 디자인 선호 이미지 적용 형용사를 추출하여 제품 개발의 방향성을 설정하였다. 본 연구를 통해 현 주얼리의 시장분석을 통한 Semiprecious Stone 제품 개발의 필요성과 가능성을 찾아 볼 수 있었다.